2006
DOI: 10.1128/mcb.01127-06
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Myocilin Nonsecretion In Vivo Is Not Sufficient To Cause Glaucoma

Abstract: Glaucoma is a leading cause of blindness, affecting over 70 million people worldwide. Vision loss is the result of death of the retinal ganglion cells. The best-known risk factor for glaucoma is an elevated intraocular pressure (IOP); however, factors leading to IOP elevation are poorly understood. Mutations in the MYOC gene are an important cause of open-angle glaucoma. Over 70 MYOC mutations have been identified, and they lead to approximately 5% of all primary open-angle glaucoma cases. Nevertheless, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…Although the exact mechanisms are still not clear, it has been suggested that accumulation of mutated myocilin induces the unfolded protein response, makes cells more sensitive to oxidative stress, and, consequently, leads to deterioration of trabecular meshwork function and/or trabecular meshwork cell death (40 -42). At the same time, no other phenotypes have been reported in humans carrying MYOC mutations or in mice expressing mutated myocilin (43)(44)(45). Myoc-null mice appeared to be normal and do not develop glaucoma, but careful analysis of non-ocular phenotypes have not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanisms are still not clear, it has been suggested that accumulation of mutated myocilin induces the unfolded protein response, makes cells more sensitive to oxidative stress, and, consequently, leads to deterioration of trabecular meshwork function and/or trabecular meshwork cell death (40 -42). At the same time, no other phenotypes have been reported in humans carrying MYOC mutations or in mice expressing mutated myocilin (43)(44)(45). Myoc-null mice appeared to be normal and do not develop glaucoma, but careful analysis of non-ocular phenotypes have not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Several mouse models of myocilin and optineurin-related POAG have been generated and will facilitate further studies of the biological mechanisms of vision loss in glaucoma. 43,44,59,89 In contrast, for complex genetic forms of disease, an individual genetic risk factor for POAG is not capable of causing glaucoma on its own, and most carriers of this type of risk factor will never develop glaucoma. In the future, when more of these risk factors have been identified, testing patients for the presence of several genetic factors may have more clinical utility for predicting which patients are at highest risk for developing disease and need closer surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…52 Expression of mutated mouse myocilin Y423H corresponding to the Y437H human mutant in the mouse TM in vivo did not lead to the activation of UPR as judged by unchanged levels of several markers including GRP78. 34 Here we used stably transfected HEK293 cells expressing wild-type and mutated myocilins under an inducible promoter to demonstrate that both mutations that we used, Y437H and I477N, induced UPR, with the I477N mutant producing higher activation of UPR markers (GRP78 and PDI) than the Y437H mutant. We do not believe that higher activation of UPR markers by the I477N mutant was due to the presence of the C-terminal FLAG tag, which was also present in wild-type myocilin.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 However, the expression of mutated myocilin allele (Tyr423His) specifically in the mouse iridocorneal angle did not lead to detectable TM cell death. 34,35 Environment may contribute to the effects of mutated myocilin. In particular, it is well established that oxidative stress may be a factor in the progression of many diseases, including glaucoma.…”
mentioning
confidence: 99%